Simultaneous Viewing of Individual Cells and Ambient Microvasculature Using Optical Absorption and Fluorescence Contrasts - Zhixing Xie; Sung-Liang Chen; Mario L. Fabiilli; J. Brian Fowlkes; K. Kirk Shung; Qifa Zhou; Paul L. Carson; Xueding Wang (Molecular Imaging)
Viewing individual cells and ambient microvasculature simultaneously is crucial for understanding tumor angiogenesis and microenvironments. We developed a confocal fluorescence microscopy (CFM) and photoacoustic microscopy (PAM) dual-modality imaging system that can assess fluorescent contrast and optical absorption contrast in biologic samples simultaneously. After staining tissues with fluorescent dye at an appropriate concentration, each laser pulse can generate not only sufficient fluorescent signals from cells for CFM but also sufficient photoacoustic signals from microvessels for PAM. To explore the potential of this system for diagnosis of bladder cancer, experiments were conducted on a rat bladder model. The CFM image depicts the morphology of individual cells, showing not only large polygonal umbrella cells but also intracellular components. The PAM image acquired at the same time provides complementary information on the microvascular distribution in the bladder wall, ranging from large vessels to capillaries. This device provides an opportunity to realize both histologic assay and microvascular characterization simultaneously. The combination of the information of individual cells and local microvasculature in the bladder offers the capability of envisioning the viability and activeness of these cells and holds promise for more comprehensive study of bladder cancer in vivo.